Plasma Levels of Macrophage Migration Inhibitory Factor and d-Dopachrome Tautomerase Show a Highly Specific Profile in Early Life - Roger, Thierry; Schlapbach, Luregn J.; Schneider, Anina; Weier, Manuela; Wellmann, Sven; Marquis, Patrick; Vermijlen, David; Sweep, Fred C. G. J.; Leng, Lin; Bucala, Richard; Calandra, Thierry; Giannoni, Eric (Frontiers in Immunology, 2017)
Macrophage migration inhibitory factor (MIF) is a pleiotropic, constitutively expressed, proinflammatory cytokine and an important regulator of immune responses. D-dopachrome tautomerase (DDT), a newly described member of the MIF protein superfamily, shares sequence homology and biological activities with MIF. We recently reported that high expression levels of MIF sustain innate immune responses in newborns. Here we elected to further characterize age-dependent MIF expression and to define whether DDT shares a similar expression profile with MIF. Therefore, we delineated the circulating concentrations of MIF and DDT throughout life using a large cohort of 307 subjects including fetuses, newborns, infants, children and adults. Compared to levels measured in healthy adults (median: 5.7 ng/ml for MIF and 16.8 ng/ml for DDT), MIF and DDT plasma concentrations were higher in fetuses (median: 48.9 and 29.6 ng/ml,), increased further at birth (median: 82.6 and 52.0 ng/ml), reached strikingly elevated levels on postnatal day 4 (median: 109.5 and 121.6 ng/ml), and decreased to adult levels during the first months of life. A strong correlation was observed between MIF and DDT concentrations in all age groups (R = 0.91, p < 0.0001). MIF and DDT levels correlated with concentrations of vascular endothelial growth factor, a protein upregulated under low oxygen tension and implicated in vascular and lung development (R = 0.70, P < 0.0001 for MIF, and R = 0.65, P < 0.0001 for DDT). In very preterm infants, lower levels of MIF and DDT on postnatal day 6 were associated with an increased risk of developing bronchopulmonary dysplasia and late-onset neonatal sepsis. Thus, MIF and DDT plasma levels show a highly specific developmental profile in early life, supporting an important role for these cytokines during the neonatal period.